KONSEP PENDIDIKAN AKHLAK DALAM SYI’IR MITRA SEJATI KARYA KH. BISRI MUSTOFA DAN RELEVANSINYA TERHADAP PENDIDIKAN AGAMA ISLAM - Zamir Muhammad Maula; Muhammad Hanief; Nur Hasan (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
The development of technology and information in the present era has not only had a positive impact but also has a negative impact on the young generation of the Indonesian people. Adding to that, the local culture of Muslim societies is contaminated with western culture, and in the end local culture increases the shock and gets closer to the western lifestyle. This is clearly reflected in the decline of most Indonesian Muslims today, especially among teenagers. A hedonic lifestyle, free sex and medicine has become a common spectacle among the public. Therefore, planting moral values from an early age is an effective way of overcoming national morals. One way that can be passed is through planting moral values in the original partner syi'ir by KH. Bisri Mustofa.